2007
DOI: 10.1080/17450390601106655
|View full text |Cite
|
Sign up to set email alerts
|

Effects ofEnterococcus faeciumand dried whey on broiler performance, gut histomorphology and intestinal microbiota

Abstract: The experiment was conducted to study the effects of supplementing a broiler starter diet with the probiotic Enterococcus faecium NCIMB 10415 and dried whey (80% lactose) on chick performance, gut histomorphology and intestinal microbiota. One-day-old male Ross 308 strain broiler chickens were fed diets containing: (i) control feed, (ii) control + 3.5% dried whey, (iii) control + 0.2% E. faecium, and (iv) control + 3.5% dried whey + 0.2% E. faecium. Birds were maintained in battery brooders confined in an envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
89
4
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(117 citation statements)
references
References 14 publications
17
89
4
7
Order By: Relevance
“…On the other hand, Szasz, (2002), Ware and Zinn (2005) reported that Fibrozyme inclusion to the steers or heifer's diets increased total tract digestibility of NDF and ADF and increased DMI and average daily gain. Few workers concluded improved feed intake, feed conversion rate, daily weight gain and total body weight in sheep, goat and cattle on administration of DFM (Torres-Rodriguez et al, 2007;Samli et al, 2007;Casey et al, 2007). Improvement from DFM supplementation could be anticipated due to positive effects on various digestive processes, especially cellulolysis, synthesis of microbial protein, stabilizers of ruminal pH and lactate, increased absorption of some nutrients and displayed a growth-promoting effect.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Szasz, (2002), Ware and Zinn (2005) reported that Fibrozyme inclusion to the steers or heifer's diets increased total tract digestibility of NDF and ADF and increased DMI and average daily gain. Few workers concluded improved feed intake, feed conversion rate, daily weight gain and total body weight in sheep, goat and cattle on administration of DFM (Torres-Rodriguez et al, 2007;Samli et al, 2007;Casey et al, 2007). Improvement from DFM supplementation could be anticipated due to positive effects on various digestive processes, especially cellulolysis, synthesis of microbial protein, stabilizers of ruminal pH and lactate, increased absorption of some nutrients and displayed a growth-promoting effect.…”
Section: Discussionmentioning
confidence: 99%
“…The use of probiotics is expected to improve BW gain, feed conversion and health of livestock because probiotics promote the establishment of a beneficial gut flora and inhibit the growth of pathogenic bacteria in the intestine. Many researchers have studied the use of lactobacilli and streptococci as probiotics (Fuler, 1989), especially enteroccocus probiotics (Fleige et al, 2007;Samli et al, 2007Vahjen et al, 2007. Some probiotic compounds are claimed to have formulae designed to provide suitable conditions in the alimentary tract so as to minimize the incidence of diarrhoea, therefore effecting improvements in body weight gain, body height and general health condition.…”
mentioning
confidence: 99%
“…It has been shown that increased lactate concentration often decreases intestine pH and is a potent anti-microbial substance to several pathogenic species such as E. coli (Samli et al, 2007). The Bifidobacterium and Lactobacillus colonizing the intestine have been reported to deliver enzymes, thus increasing the intestine digestive enzyme activity (Sissons, 1989).…”
Section: Discussion:-mentioning
confidence: 99%